Understanding the Politics of Perikles Around 450 BC. The Benefits of an Economic Perspective - Carl Hampus Lyttkens; Henrik Gerding (Lund University, School of Economics and Management, Department of Economics, 2015)
Perikles is usually seen as a great statesman and clever leader of the Athenians. In the mid fifth century BC, he seems however to have been in serious political trouble and may well have been in danger of losing the struggle for power and of being ostracised. The fact that his incentives changed considerably at this point in time is ignored in traditional historical accounts. In contrast, we see the fierce competition as a motivation for several important policy measures introduced by Perikles at this particular time: the pay to jurors, the new law on citizenship (which has been a puzzle to many historians), and the building projects on the Acropolis and elsewhere. Compared to traditional analyses, an economic rational-actor approach thus provides a diachronic analytical benefit by focusing on the way incentives change over time and it provides a synchronic benefit by dealing with various decisions in a common framework.
Keywords: B40; K37; N43; 330; economics; ancient history; Athens; Perikles; law on citizenship; Parthenon; payment to jurors